Reciprocity in Free Trade Agreements - Freund, Caroline (World Bank, Washington, DC, 2014)
The author uses detailed trade, tariff, and income data for countries involved in 91 trade agreements negotiated since 1980 to test for reciprocity in free trade agreements. The results offer strong evidence of reciprocity in North-North and South-South free trade agreements, but there is little empirical support for reciprocity in North-South trade agreements. In particular, after controlling for other determinants of trade preferences, the results suggest that a one percent increase in preferences offered leads to about a one-half of a percent increase in preferences received in North-North and South-South trade agreements. Freund also finds evidence that large countries extract greater trade concessions from small countries. This leads to a modified form of reciprocity in North-South agreements. A large increase in access to a developing country market leads to only a small increase in access to a rich country market. The results imply that there are incentives for countries to maintain protection in order to extract more concessions from trade partners. But in general, such perverse incentives should be less of a concern in developing countries involved in North-South agreements because the value of a developing country tariff preference in terms of its effect on trade preferences from a rich country is quite small. The gains from unilateral liberalization are likely to far outweigh potential gains from using protection as a bargaining chip in trade negotiations. The evidence is consistent with a repeated game model of trade liberalization. The model presented shows that trade preferences granted are increasing in trade preferences received. This implies that countries can extract greater concessions from trade agreement members if they have higher external trade barriers. However, if a country's trade barriers are very large then the gains from reneging on the agreement in the short run will be high, making the agreement unenforceable despite offering long-term gains. So, there is a reciprocity-credibility tradeoff. High tariffs may allow countries to extract more concessions from potential trade agreement partners, but they also make the country less credible in actually implementing agreed tariff concessions. If a country's external tariff is very high relative to other countries, then it will not be able to commit credibly to any free trade agreement.